Classification of Student Reasoning Skills in Solving Mathematics Problems in Elementary School - Joko Sulianto; Sunardi Sunardi; Sri Anitah; Gunarhadi Gunarhadi (Jurnal Pendidikan Indonesia, 2020)
The purpose of this study was to describe the classification of students' reasoning abilities in solving mathematical problems in elementary schools. The focus of this study is the classification of students' reasoning abilities in solving mathematical problems in the elementary schools of the city of Semarang. This study uses a qualitative approach. The Research subject is elementary school students at Tambakrejo Elementary School Semarang. Data is taken using tests. Based on data analysis, the reasoning classification is as follows: 36.25% understand the meaning in low categories, 37.5% think logically in low categories, 31.1% understand negative examples in low categories, 17.05% think deductions in very low category, 18.15% think systematically in very low categories, 31.65% think consistently in low category, 34.85% make excuses and determine strategies in low category, 49.85% determine method in low category, and 24.3% draw conclusions in low category. Thus the reasoning ability of students is low, students have not been able to think logically to make connections between empirical facts and the problems faced so they are not able to draw conclusions, students have not been able to do the thinking process to make arguments so that new statements are based on facts, it is necessary to develop learning models to improve mathematical reasoning of elementary school students